Engineered self-standing monolithic Cu-Zn-Ni oxide nanocubes as battery materials for durable all-solid-state hybrid supercapacitor devices. (July 2023) - Bahnasawy, Nour; Sayed, Doha M.; Allam, Nageh K.
Abstract: The optimum energy storage performance can be attained by combining the advantages of battery and capacitor into one device. This could be fulfilled by the smart design of positive (battery-like) and negative (EDL) electrode materials in a solid-state supercapattery. In this study, a cheap, yet effective, and simple strategy is utilized to synthesize binder-free, ternary metal oxide nanoparticles based on earth-abundant elements, namely Cu, Zn, and Ni. A monolithic sub-100 nm mixed oxide is prepared by anodizing German silver alloy (Cu–Zn–Ni) in an aqueous electrolyte for various time intervals (2, 5, and 8 min). Upon analyzing the electrochemical performance of the films as positive electrodes in 1 M KOH, the 5 min anodized film (CZNO-5), with an elemental composition of Cu4 Zn2 NiOx @Cu-Zn-Ni, depicts remarkable areal and volumetric capacitances of 27 mF/cm 2 and 3150 F/cm 3, respectively, at a current density of 1 mA/cm 2 . The assembled solid-state supercapattery device made of CZNO-5 and bioderived activated carbon (B-AC) exhibits 3.8 mF/cm 2 at 1 mA/cm 2 with 35 % rate capability at 5 mA/cm 2 . The specific energy and specific power of the CZNO-5//B-AC device are found to be 0.97 μW h/cm 2 and 0.91 mW/cm 2, respectively. Most importantly, unlike many Cu-based devices, CZNO-5//B-AC shows an eminent durability with 100 and 89.6 % retention of the first cycle capacitance after 3800 and 5000 successive charge/discharge cycles. Highlights: A monolithic Cu–Zn-Ni-O nanocube was prepared via anodization of German silver alloy. The material revealed remarkable areal and volumetric capacitances. The CZNO-5//B-AC device exhibited 3.8 mF/cm 2 at 1 mA/cm 2 . The device showed 100 and 89.6 % retention of the first cycle capacitance after 3800 and 5000 charge/discharge cycles.